Lower gastrointestinal endoscopy in elderly: A single-center experience - ERGENÇ, MUHAMMER; UPRAK, TEVFİK KIVILCIM (My University, 2022)
INTRODUCTION: Endoscopic procedures are frequently applied to the elderly population over 65, with the increased population of this age group. The comorbidities of this population are thought to be increased risk factors for endoscopic interventions. We need more literature on applying lower gastrointestinal endoscopy in the aged. This study aimed to evaluate the efficacy and safety of lower gastrointestinal endoscopy in the elderly population.METHODS: We performed a retrospective observational study of patients over 65 who underwent lower gastrointestinal endoscopy from January 2016 to January 2021 at the Istanbul Sultanbeyli State Hospital Endoscopy Unit. This study was approved by the local Ethics Committee and registered with ClinicalTrials.gov (NCT05012527). A total of 564 patients\" following parameters were analyzed: indications, endoscopic findings, histopathological findings, and complications of lower gastrointestinal endoscopy.RESULTS: The cecal intubation rate was 90% in colonoscopies. The inadequate bowel cleansing rate was 12,4% in colonoscopies and 13% in all lower endoscopy procedures. There was 6 percent malignancy detected. The polyp detection rate is approximately 45% in colonoscopies, and polyps are seen mainly left side of the colon. The overall diagnostic yield rate is 48.7%, and colorectal cancer (CRC) yield is 5.9% on colonoscopies. The complication rate was 1.2%.DISCUSSION AND CONCLUSION: This study showed that colonoscopy in the elderly has a high diagnostic yield and can be applied safely.

GİRİŞ ve AMAÇ: Endoskopik işlemler, bu yaş grubunun artan nüfusu ile birlikte 65 yaş üstü hastalarda sıklıkla uygulanmaktadır. Bu popülasyonda komorbiditelerin endoskopik girişimler için esktra risk oluşturduğu düşünülmektedir. Bu çalışma, yaşlı popülasyonda alt gastrointestinal endoskopinin etkinliğini ve güvenliğini değerlendirmeyi amaçlamıştır. YÖNTEM ve GEREÇLER: İstanbul Sultanbeyli Devlet Hastanesi Endoskopi Ünitesinde Ocak 2016 - Ocak 2021 tarihleri arasında alt gastrointestinal endoskopi yapılan 65 yaş üstü hastaların verileri retrospektif olarak incelendi. Bu çalışma yerel Etik Kurul tarafından onaylandı ve ClinicalTrials.gov'a (NCT05012527) kaydedildi. Toplam 564 hastanın sıralanan parametreleri analiz edildi: Endikasyonlar, endoskopik bulgular, histopatolojik bulgular ve alt gastrointestinal endoskopi komplikasyonları. BULGULAR: Kolonoskopilerde çekal entübasyon oranı %90 olarak saptandı. Yetersiz barsak temizliği oranı kolonoskopilerde %12,4 ve tüm alt gastrointestinal endoskopi işlemlerinde %13 saptandı. Yüzde 6 malignite tespit edildi. Kolonoskopilerde polip görülme oranı yaklaşık %45 idi ve polipler ağırlıklı olarak kolonun sol tarafında tespit edildi. Kolonoskopilerde genel tanı verimi %48,7 ve kolorektal kanser tanı koyma oranı %5,9 saptandı. Komplikasyon oranı %1.2 idi. TARTIŞMA ve SONUÇ: Bu çalışma, kolonoskopinin yüksek tanısal verime sahip olduğunu ve yaşlı hastalarda güvenle uygulanabileceğini göstermiştir.
Yaşlılarda alt gastrointestinal endoskopi: Tek merkez deneyimi
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); colonoscopy; rectosigmoidoscopy; proctoscopy; elderly; aged; kolonoskopi; rektosigmoidoskopi; proktoskopi; yaşlı hasta; yaşlılık